Aquaporin-4 Inhibition Mediates Piroxicam-Induced Neuroprotection against Focal Cerebral Ischemia/Reperfusion Injury in Rodents - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R.; Yavagal D.R. (My University, 2025)
Background and Purpose:Aquaporin-4(AQP4) is an abundant water channel protein in brain that regulates water transport to maintain homeostasis. Cerebral edema resulting from AQP4 over expression is considered to be one of the major determinants for progressive neuronal insult during cerebral ischemia. Although, both upregulation and downregulation of AQP4 expression is associated with brain pathology, over expression of AQP4 is one of the chief contributors of water imbalance in brain during ischemic pathology. We have found that Piroxicam binds to AQP4 with optimal binding energy value. Thus, we hypothesized that Piroxicam is neuroprotective in the rodent cerebral ischemic model by mitigating cerebral edema via AQP4 regulation.Methods:Rats were treated with Piroxicam OR placebo at 30 min prior, 2 h post and 4 h post 60 minutes of MCAO followed by 24 hour reperfusion. Rats were evaluated for neurological deficits and motor function just before sacrifice. Brains were harvested for infarct size estimation, water content measurement, biochemical analysis, RT-PCR and western blot experiments.Results:Piroxicam pretreatment thirty minutes prior to ischemia and four hour post reperfusion afforded neuroprotection as evident through significant reduction in cerebral infarct volume, improvement in motor behavior, neurological deficit and reduction in brain edema. Furthermore, ischemia induced surge in levels of nitrite and malondialdehyde were also found to be significantly reduced in ischemic brain regions in treated animals. This neuroprotection was found to be associated with inhibition of acid mediated rise in intracellular calcium levels and also downregulated AQP4 expression.Conclusions:Findings of the present study provide significant evidence that Piroxicam acts as a potent AQP4 regulator and renders neuroprotection in focal cerebral ischemia. Piroxicam could be clinically exploited for the treatment of brain stroke along with other anti-stroke therapeutics in future. © 2013 Bhattacharya et al.